Aggressive and Disruptive Behavior Among Psychiatric Patients With Major Depressive Disorder, Schizophrenia, or Alcohol Dependency and the Effect of Depression and Self-Esteem on Aggression - Fritz, Michael; Shenar, Riad; Cardenas-Morales, Lizbeth; Jäger, Markus; Streb, Judith; Dudeck, Manuela; Franke, Irina (Frontiers in Psychiatry, 2020)
Aggressive and disruptive behavior in inpatient settings poses a serious challenge for clinical staff and fellow patients. Hence, the aim of this study was to identify different aspects of aggressive and disruptive behavior in the context of an aberrant self-esteem or clinically manifested depression as potentially influencing factors. We collected self-reported data from 282 psychiatric patients (ICD-10 diagnoses for alcohol dependency, schizophrenia or major depressive disorder (MDD)) and compared it to healthy norm groups. As expected, all three patient groups scored higher in the aggression questionnaires than the norm group. Specifically, patients with MDD exhibited significantly higher externally directed aggression, reactive aggression, and irritability compared to controls. Patients with schizophrenia displayed higher irritability, while all three groups showed distinctly higher self-aggressiveness than healthy persons. We found a lower inhibition of aggression in alcohol dependent subjects compared to both the patient groups and the norm sample. Yet, the higher the self-esteem among alcohol dependent and MDD patients, the lower were their aggression scores; similarly, a lower self-esteem among patients diagnosed with schizophrenia resulted in heighten self-aggressiveness. Thus, our data suggests that therapeutic interventions for strengthening self-esteem in patients with a diagnosis of MDD, alcohol dependency or schizophrenia could reduce certain aspects of aggressive behavior. Therefore, it seems conceivable that strengthening self-esteem in psychiatric patients could contribute to the prevention of violence in clinical practice.